Pengaruh e-learning terhadap motivasi dan hasil belajar siswa MI NU Miftahul Huda 01 Sudimoro Karangmalang Gebog Kudus - Noor Akhlis; Fatchurrohman Fatchurrohman (At Turots: Jurnal Pendidikan Islam, 2022)
This study aims as follows: 1) To determine the effect of e-learning on student motivation at MI NU Miftahul Huda 01 Sudimoro Karangmalang Gebog Kudus; 2) To find out the effect of e-learning on student learning outcomes of MI NU Miftahul Huda 01 Sudimoro Karangmalang Gebog Kudus; 3) To find out the effect of e-learning on the motivation and learning outcomes of MI NU Miftahul Huda 01 Sudimoro Karangmalang students, Gebog Kudus.  This study is a quantitative study using correlational analysis, to find out whether there is an effect of e-learning on student motivation and learning outcomes at MI NU Miftahul Huda 01 Sudimoro Karangmalang Gebog Kudus in 2021, using t-test analysis.  The results of the research are 1) E-learning has a positive and significant effect on student motivation at MI NU Miftahul Huda 01 Sudimoro Karangmalang Gebog Kudus. This is evidenced by the Wilcoxon test, the results of e-learning t-count are 48.347, and t-table is 1.706, while p=0.00 < 0.05, then Ha is accepted and Ho is rejected. While the results of tcount motivation are 67,457, and ttable are 1,706, while p=0.00 < 0.05, then Ha is accepted and Ho is rejected; 2) E-learning has a positive and significant effect on student learning outcomes of MI NU Miftahul Huda 01 Sudimoro Karangmalang Gebog Kudus. This is evidenced by the Wilcoxon test, the results of e-learning t-count are 48.347, and t-table is 1.706, while p=0.00 < 0.05, then Ha is accepted and Ho is rejected. While the results of tcount learning outcomes are 31,457, and ttable is 1,706, while p=0.00 < 0.05, then Ha is accepted and Ho is rejected; 3) E-learning has a positive and significant effect on the motivation and learning outcomes of MI NU Miftahul Huda 01 Sudimoro Karangmalang students, Gebog Kudus. This is evidenced by the Wilcoxon test, the results of e-learning t-count are 48.347, and t-table is 1.706, while p=0.00 < 0.05, then Ha is accepted and Ho is rejected. Meanwhile, the results of tcount motivation are 67,457, and ttable are 1,706, while p=0.00 < 0.05, then Ha is accepted and Ho is rejected. While the results of tcount learning outcomes are 31,457, and ttable is 1,706, while p=0.00 < 0.05, then Ha is accepted and Ho is rejected